1972
DOI: 10.1084/jem.136.6.1581
|View full text |Cite
|
Sign up to set email alerts
|

DISTRIBUTION OF LABELED LYMPH NODE CELLS IN MICE DURING THE LYMPHOCYTOSIS INDUCED BY BORDETELLA PERTUSSIS

Abstract: The mechanism by which Bordetella pertussis organisms and their products induce lymphocytosis in mice was analyzed in terms of the localization of syngeneic Cr-51-labeled lymph node cells. Labeled lymphoid cells incubated in vitro with the supernatant of B. pertussis cultures and then injected intravenously into normal recipients, or labeled cells injected into pertussis-treated recipients were unable to "home" to lymphoid organs but persisted for long periods in the blood. In animals "equipped" with a populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…These results are consistent with those observed for CBA/J mice, which also exhibit a marked leukocytosis despite being resistant to histamine sensitization (40).…”
Section: Resultssupporting
confidence: 82%
“…These results are consistent with those observed for CBA/J mice, which also exhibit a marked leukocytosis despite being resistant to histamine sensitization (40).…”
Section: Resultssupporting
confidence: 82%
“…He found that PBL isolated from pertussis-treated mice migrated to tissues and lymph nodes at much lower levels than PBL isolated from control mice, and concluded that the inhibition of lymphocyte emigration from the circulation in pertussis-treated mice is due to an effect on the lymphocytes themselves and not on the tissues (Morse and Barron 1970). In a follow-up study using a similar approach, he found that labeled lymphocytes had reduced homing to lymphoid tissue whether the lymphocytes or the recipient mice were treated with pertussis lymphocytosis-promoting factor (LPF) (Taub et al 1972). He also found that LPF could bind to erythrocytes and lymphocytes and then spontaneously elute from these cells to affect other cells, and proposed this as a possible explanation for the inhibitory effect when LPF was injected into recipient mice (Taub et al 1972;Adler and Morse 1973).…”
Section: Studies Of Stephen Morsementioning
confidence: 86%
“…In a follow-up study using a similar approach, he found that labeled lymphocytes had reduced homing to lymphoid tissue whether the lymphocytes or the recipient mice were treated with pertussis lymphocytosis-promoting factor (LPF) (Taub et al 1972). He also found that LPF could bind to erythrocytes and lymphocytes and then spontaneously elute from these cells to affect other cells, and proposed this as a possible explanation for the inhibitory effect when LPF was injected into recipient mice (Taub et al 1972;Adler and Morse 1973). Using histopathology analysis, he found early massive depletion of lymphocytes from the spleen, and to a lesser extent from the thymus, in LPF-treated mice and subsequent depletion of lymphocytes from lymph nodes (Athanassiades and Morse 1973).…”
Section: Studies Of Stephen Morsementioning
confidence: 99%
“…We speculated that the enzymatic activity detected in plasma was likely released from cellular elements, that is, RBCs, that serve as depots of Ptx toxin 6 and could explain its protracted effect on cells. This turned out to be true (data not shown).…”
Section: Other Ptx-elicited Effectsmentioning
confidence: 99%
“…In vivo, Ptx causes lymphocytosis by inhibiting lymphocyte migration from blood to tissues, or across lymph node endothelium. [5][6][7][8] In mature leukocytes, chemotactic receptors and their ligands signal through G proteins, and such signaling is essential for their adhesion and directed migration to inflammatory sites. This G protein-dependent effect is suppressed by Ptx.…”
Section: Introductionmentioning
confidence: 99%